2008
DOI: 10.1038/oby.2008.10
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hepatic Mitochondrial Compartment in a Model of Obesity and Insulin Resistance

Abstract: The objective of this paper is to evaluate adaptations in hepatic mitochondrial protein mass, function and efficiency in a rat model of high-fat diet-induced obesity and insulin resistance that displays several correlates to human obesity. Adult male rats were fed a high-fat diet for 7 weeks. Mitochondrial state 3 and state 4 respiratory capacities were measured in liver homogenate and isolated mitochondria by using nicotinamide adenine dinucleotide, flavin adenine dinucleotide and lipid substrates. Mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 27 publications
10
70
1
2
Order By: Relevance
“…Despite the fact that the NP and LP diets are isocaloric, genes involved in energy metabolism, oxidative phosphorylation, and other mitochondrial genes were the ones most over represented on the list of changed gene sets (Tables 3 and 4). However, as CS activity can be considered a measure of mitochondrial mass (22), the results suggests a dysregulation of gene expression related to mitochondrial function rather than a change in mitochondrial mass. This may be in contrast to studies by Park et al (26), who found a significant decrease in mtDNA:gDNA ratio in both liver and skeletal muscle in 5-wk-old offspring of maternal LP rats.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Despite the fact that the NP and LP diets are isocaloric, genes involved in energy metabolism, oxidative phosphorylation, and other mitochondrial genes were the ones most over represented on the list of changed gene sets (Tables 3 and 4). However, as CS activity can be considered a measure of mitochondrial mass (22), the results suggests a dysregulation of gene expression related to mitochondrial function rather than a change in mitochondrial mass. This may be in contrast to studies by Park et al (26), who found a significant decrease in mtDNA:gDNA ratio in both liver and skeletal muscle in 5-wk-old offspring of maternal LP rats.…”
Section: Discussionmentioning
confidence: 91%
“…As a measure of the mitochondrial fraction of tissue mass, citrate synthase (CS) specific enzyme activity and mRNA level (22) was determined in liver and skeletal muscle of the newborn pups. There was no difference between diet groups in either CS mRNA levels (Table S1, http://links.lww.com/PDR/A56) or CS enzyme specific activities (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported increased respiration in the liver mitochondria of obesity models (17,54), and other models of obesity have exhibited decreased respiration in liver (55). Therefore, we carried out oxygen consumption experiment in purified mitochondria from our HFD model.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that various mitochondrial factors are of paramount importance in the pathogenesis of diabetes. For example, high fat diet-induced alterations in the mitochondrial compartment are associated with the development of insulin resistance and ectopic fat storage in liver (5). The dysfunction of mitochondria damages the pancreatic ␤-cells and contributes to the development of a hyperglycemic status (6).…”
Section: Type 2 Diabetes (T2d)mentioning
confidence: 99%